ANALISIS YURIDIS TERKAIT WANPRESTASI ATAS KREDIT MACET PADA PERKARA PERDATA DI PERBANKAN INDONESIA - Ayu Tri Wulan; Deny Haspada; Edy Santoso (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2022)
The problems in writing the thesis are what are the forms of efforts to rescue bad loans according to the provisions of Bank Indonesia, what are the mechanisms used by banks in resolving bad loans, what are the legal consequences for debtors who default on credit agreements of PT Bank Mandiri, PT Bank BNI and PT Bank Banten. The purpose of this study is to find out the answers to the problems discussed. The research method used in this writing, the author uses 2 (two) methods: first, library research, namely by conducting research on various reading sources, namely books, legal magazines, opinions of scholars, legislation and other materials. studying. The second field research (Field Research) is to do spaciousness in this case the author directly conducts a study at PT Bank Mandiri, PT Bank BNI and PT Bank Banten, Default is a situation where one party does not fulfill its obligations, is late or does not fulfill its obligations. The state of default is different from the situation beyond the power or ability of the party who is unable to carry out his obligations. This default can occur due to intentional, negligence, without error. The term default is a breach of contract, while the form of a debtor's default can be in the form of: the debtor does not fulfill the performance at all, the debtor fulfills the performance, but not as agreed, the debtor fulfills the performance but does not fulfill the agreement. time (too late), the debtor does something that requires the agreement not to be carried out. It can be concluded that there are forms of default that occur in the implementation of the agreement. Where the parties sometimes default in the form of being late in paying what was agreed upon or not making payments, resulting in a loss to one of the parties. With this loss, the aggrieved party can claim compensation for the loss suffered in the ways determined by law.